IMPLEMENTATION OF INTEGRATED MARKETING COMMUNICATION PROJECT FOR STARCAM TO ENHANCE BRAND AWARENESS - Alit Bimaseto; Tasya Hardiyanto; Nathania Elizabeth (Program Pascasarjana UIN Sumatera Utara, 2026)
The rapid growth of digital technology has increased demand for high-quality sports documentation, particularly among Indonesia’s mini soccer communities. Starcam offers an Artificial Intelligence (AI)-based sports videography service using auto-tracking camera technology to record football matches automatically. However, limited public awareness and understanding of AI-powered sports videography have constrained the adoption of this service. This project aimed to develop and implement an Integrated Marketing Communication (IMC) strategy to enhance Starcam’s brand awareness in Pekanbaru. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation involving Starcam management and members of the local mini soccer community. The project was designed using the Integrated Marketing Communication framework, supported by the AISAS model to examine digital consumer behavior and the SOSTAC planning framework to formulate marketing strategies. The findings reveal that the primary challenge lies not in the technology itself but in the low level of public understanding regarding the benefits and value proposition of AI-based sports videography. Based on these findings, the project proposes an integrated communication strategy consisting of market education, digital storytelling, social media optimization, collaboration with football communities, and flexible service packages. These initiatives are expected to strengthen Starcam’s brand awareness, increase consumer engagement, and encourage wider adoption of AI-based sports videography services among amateur football communities in Pekanbaru.